Hubungan Indonesia-Malaysia: Memerlukan Perspektif dan Kebijakan Baru? - Djafar, Zainuddin (Indonesian Journal of International Law, 2006)
The relationship between Indonesia-Malaysia in 2005 and 2006 id quite problematic concerning three main issues: illegal migrant, illegal logging, and Ambalat’s dispute. Historically, there were disputes which broke up the relationship between the two countries in 1963 until 1966. Forty years later (1996-2006), three main issues occured, which have no correlation with formerly disputes. Those issues have become significant after Indonesia entered multidimensional crisis in 1997-1999 and the effects remain. At the other side, Malaysia has reached rapid growth in economic, business, manufacture, and financial in the last past seven years. These two realities of circumstances have become Indonesia and Malaysia position background, considering their own self as the right one of the three sensitive issues. The reconstruct of a good, close, and maximal neighbourhood between the two countries is really expected. This article observes the needed of consideration from Indonesia on policy aspect and new perspective in facing pressure from Malaysia. It is obvious that those matters are the consequences for the establishment of an advantage relationship between the two countries.